Stravaganza : city of ships - Hoffman, Mary (Bloomsbury, 2012)
Feeling inferior to her talented twin brother, teenaged Isabel is transported to a parallel world that resembles the Italian Renaissance city-state of Ravenna, where she tries to save the city from attack by the fierce Gate people.